2018
DOI: 10.18471/rbe.v32.25470
|View full text |Cite
|
Sign up to set email alerts
|

Importância De Oportunidades De Desenvolvimento E Apoio Institucional Na Satisfação Acadêmica De Enfermeiros

Abstract: Como citar este artigo: Alves FC, Apostólico MR, Pina-Oliveira AA, Puggina ACG. Importância de oportunidades de desenvolvimento e apoio institucional na satisfação acadêmica de enfermeiros. Rev baiana enferm. 2018;32:e25470.Objetivos: identificar a satisfação acadêmica de enfermeiros assistenciais e associar características sociodemográficas, educacionais e profissionais do enfermeiro com a sua satisfação acadêmica. Método: estudo analítico transversal realizado com enfermeiros. Foram utilizados dois questioná… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A Brazilian study with nursing students has identified that one of the causes of higher stress and lesser satisfaction for them was their relationship with professors (20)(21) . Given this, interpersonal relationships with professors may be less conflicted in the integrated curriculum, since students are the protagonists of their education, whereas professors are facilitators of this process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Brazilian study with nursing students has identified that one of the causes of higher stress and lesser satisfaction for them was their relationship with professors (20)(21) . Given this, interpersonal relationships with professors may be less conflicted in the integrated curriculum, since students are the protagonists of their education, whereas professors are facilitators of this process.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional curriculum, on the other hand, uses a passive methodology, in which the professor is responsible for conveying knowledge and the students have little autonomy to develop their skills. This absence of independent interaction leads to dissatisfaction (21) and, consequently, interpersonal conflicts.…”
Section: Discussionmentioning
confidence: 99%